Guía para la implementación de la norma ISO 9001:2008 para establecimientos farmacéuticos a partir del instrumento de verificación contemplado en la Resolución 0444 del 2008 (2012)
The purpose of this guide is to show a basic model that allows design and implement a system of quality management ISO 9001:2008 with the Good Manufacturing Practices (BPE) existing in the Colombian pharmaceutical industry. This project which has been called "Guidelines for the implementation of ISO 9001:2008 for Pharmaceutical Establishments from the verification instrument referred to in Resolution 0444 of 2008", is aimed especially at those who provide pharmaceutical services under the name Mixtures of Central parenteral, focusing on certification under ISO 9001 for the attention of the users. Pharmaceutical establishments face daily challenges which bring into play complex survival of health systems. To do this, management systems are required agile and modern, tailored to meet needs not only of customers, patients and / or users, also from the regulatory authorities and other stakeholders. The guide was made from the activities in pharmaceutical services covered by the resolution 0444 of 2008 published by the ministry of social protection. Are specified in this harmonization and integration elements that provide insight into the similarities between the two standards and provide information on how to implement the requirements of ISO are not covered by Colombian law, thus implementing a quality management compatible and consistent with existing regulations.